A biallelic truncating AEBP1 variant causes connective tissue disorder in two siblings - Hebebrand, Moritz; Vasileiou, Georgia; Krumbiegel, Mandy; Kraus, Cornelia; Uebe, Steffen; Ekici, Arif Bülent; Thiel, Christian; Reis, André; Popp, Bernt (American Journal of Medical Genetics Part A, 2018)
Biallelic variants in the AEBP1 gene cause a novel autosomal-recessive connective tissue disorder (CTD) reminiscent of Ehlers-Danlos Syndrome (EDS). The four previously reported individuals show considerable clinical variability. Unbiased high-throughput sequencing enables the rapid identification of additional cases for such rare entities. We identified the homozygous nonsense variant c.917dup, p.Tyr306* in AEBP1 using clinical exome sequencing in a female individual with previously unsolved CTD. Segregation testing confirmed homozygosity in the clinically affected brother and heterozygous carrier status in the healthy mother. Chromosomal microarray showed that the variant lies in a run of homozygosity, suggesting a common origin of this genomic segment. RT-PCR analysis in the mother revealed a monoallelic expression of the normal transcript supporting a nonsense-mediated mRNA decay and functional nullizygosity as disease mechanism. We describe two individuals from a fourth family with AEBP1-associated CTD. Our results further verify that autosomal-recessive inherited LOF variants in the AEBP1 gene cause clinical features of different EDS subtypes, but also of the marfanoid spectrum. As identification of further individuals is necessary to inform the clinical characterization, we stress the added value of exome sequencing for such rare diseases.
EVALuna2:35120

Biallelic Expression of Mucin-1 in Autosomal Dominant Tubulointerstitial Kidney Disease: Implications for Nongenetic Disease Recognition - Knaup, Karl; Hackenbeck, Thomas; Popp, Bernt; Stoeckert, Johanna; Wenzel, Andrea; Büttner-Herold, Maike; Pfister, Frederick; Schüler, Markus; Seven, Didem; May, Annette M.; Halbritter, Jan; Gröne, Hermann Josef; et al. (Journal of the American Society of Nephrology, 2018)
BACKGROUND: Providing the correct diagnosis for patients with tubulointerstitial kidney disease and secondary degenerative disorders, such as hypertension, remains a challenge. The autosomal dominant tubulointerstitial kidney disease (ADTKD) subtype caused by MUC1 mutations (ADTKD-MUC1) is particularly difficult to diagnose, because the mutational hotspot is a complex repeat domain, inaccessible with routine sequencing techniques. Here, we further evaluated SNaPshot minisequencing as a technique for diagnosing ADTKD-MUC1 and assessed immunodetection of the disease-associated mucin 1 frameshift protein (MUC1-fs) as a nongenetic technique. METHODS: We re-evaluated detection of MUC1 mutations by targeted repeat enrichment and SNaPshot minisequencing by haplotype reconstruction via microsatellite analysis in three independent ADTKD-MUC1 families. Additionally, we generated rabbit polyclonal antibodies against MUC1-fs and evaluated immunodetection of wild-type and mutated allele products in human kidney biopsy specimens. RESULTS: The detection of MUC1 mutations by SNaPshot minisequencing was robust. Immunostaining with our MUC1-fs antibodies and an MUC1 antibody showed that both proteins are readily detectable in human ADTKD-MUC1 kidneys, with mucin 1 localized to the apical membrane and MUC1-fs abundantly distributed throughout the cytoplasm. Notably, immunohistochemical analysis of MUC1-fs expression in clinical kidney samples facilitated reliable prediction of the disease status of individual patients. CONCLUSIONS: Diagnosing ADTKD-MUC1 by molecular genetics is possible, but it is technically demanding and labor intensive. However, immunohistochemistry on kidney biopsy specimens is feasible for nongenetic diagnosis of ADTKD-MUC1 and therefore, a valid method to select families for further diagnostics. Our data are compatible with the hypothesis that specific molecular effects of MUC1-fs underlie the pathogenesis of this disease.
EVALuna2:34428

Breast MRI texture analysis for prediction of BRCA-associated genetic risk - Vasileiou, Georgia; Costa, Maria J.; Long, Christopher; Wetzler, Iris; Hoyer, Juliane; Kraus, Cornelia; Popp, Bernt; Emons, Julius; Wunderle, Marius; Wenkel, Evelyn; Uder, Michael; Beckmann, Matthias; et al. (BMC Medical Imaging, 2020)
BACKGROUND: BRCA1/2 deleterious variants account for most of the hereditary breast and ovarian cancer cases. Prediction models and guidelines for the assessment of genetic risk rely heavily on criteria with high variability such as family cancer history. Here we investigated the efficacy of MRI (magnetic resonance imaging) texture features as a predictor for BRCA mutation status. METHODS: A total of 41 female breast cancer individuals at high genetic risk, sixteen with a BRCA1/2 pathogenic variant and twenty five controls were included. From each MRI 4225 computer-extracted voxels were analyzed. Non-imaging features including clinical, family cancer history variables and triple negative receptor status (TNBC) were complementarily used. Lasso-principal component regression (L-PCR) analysis was implemented to compare the predictive performance, assessed as area under the curve (AUC), when imaging features were used, and lasso logistic regression or conventional logistic regression for the remaining analyses. RESULTS: Lasso-selected imaging principal components showed the highest predictive value (AUC 0.86), surpassing family cancer history. Clinical variables comprising age at disease onset and bilateral breast cancer yielded a relatively poor AUC ( 0.56). Combination of imaging with the non-imaging variables led to an improvement of predictive performance in all analyses, with TNBC along with the imaging components yielding the highest AUC (0.94). Replacing family history variables with imaging components yielded an improvement of classification performance of 4%, suggesting that imaging compensates the predictive information arising from family cancer structure. CONCLUSIONS: The L-PCR model uncovered evidence for the utility of MRI texture features in distinguishing between BRCA1/2 positive and negative high-risk breast cancer individuals, which may suggest value to diagnostic routine. Integration of computer-extracted texture analysis from MRI modalities in prediction models and inclusion criteria might play a role in reducing false positives or missed cases especially when established risk variables such as family history are missing.
CRIS-Team Scopus Importer:2020-08-07
Keywords: BRCA1/2; Breast cancer; HBOC; L-PCR; MRI; Texture analysis

Clinical relevance of systematic phenotyping and exome sequencing in patients with short stature - Hauer, Nadine; Popp, Bernt; Schoeller, Eva; Schuhmann, Sarah; Heath, Karen E.; Hisado-Oliva, Alfonso; Klinger, Patricia; Kraus, Cornelia; Trautmann, Udo; Zenker, Martin; Zweier, Christiane; Wiesener, Antje; et al. (Genetics in Medicine, 2018)
PurposeShort stature is a common condition of great concern to patients and their families. Mostly genetic in origin, the underlying cause often remains elusive due to clinical and genetic heterogeneity.MethodsWe systematically phenotyped 565 patients where common nongenetic causes of short stature were excluded, selected 200 representative patients for whole-exome sequencing, and analyzed the identified variants for pathogenicity and the affected genes regarding their functional relevance for growth.ResultsBy standard targeted diagnostic and phenotype assessment, we identified a known disease cause in only 13.6% of the 565 patients. Whole-exome sequencing in 200 patients identified additional mutations in known short-stature genes in 16.5% of these patients who manifested only part of the symptomatology. In 15.5% of the 200 patients our findings were of significant clinical relevance. Heterozygous carriers of recessive skeletal dysplasia alleles represented 3.5% of the cases.ConclusionA combined approach of systematic phenotyping, targeted genetic testing, and whole-exome sequencing allows the identification of the underlying cause of short stature in at least 33% of cases, enabling physicians to improve diagnosis, treatment, and genetic counseling. Exome sequencing significantly increases the diagnostic yield and consequently care in patients with short stature.
EVALuna2:34628

Common RUNX3 missense variant contributes to psoriatic arthritis by affecting splicing and modifying signaling, activation and differentiation of T-cells - Hüffmeier, Ulrike; Löhr, Sabine; Uebe, Steffen; Popp, Bernt; Bowes, J.; Kirchner, P.; Giardina, E.; Korendowych, E.; Ekici, Arif Bülent; Ho, P.; Behrens, F.; Koehm, M.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Common RUNX3 missense variant contributes to psoriatic arthritis by modifying differentiation of CD8(+) T-cells - Kerker, Iris; Löhr, Sabine; Uebe, Steffen; Popp, Bernt; Vasileiou, Georgia; Bowes, John; Kirchner, Philipp; Becker, Ina; Giardina, Emiliano; Korendowych, Eleanor; Ekici, Arif Bülent; Ho, Pauline; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2022)
CRIS-Team WoS Importer:2022-05-06

De novo and inherited variants in ZNF292 underlie a neurodevelopmental disorder with features of autism spectrum disorder - Mirzaa, Ghayda M.; Chong, Jessica X.; Piton, Amélie; Popp, Bernt; Foss, Kimberly; Guo, Hui; Harripaul, Ricardo; Xia, Kun; Scheck, Joshua; Aldinger, Kimberly A.; Sajan, Samin A.; Tang, Sha; et al. (Genetics in Medicine, 2019)
Purpose: Intellectual disability (ID) and autism spectrum disorder (ASD) are genetically heterogeneous neurodevelopmental disorders. We sought to delineate the clinical, molecular, and neuroimaging spectrum of a novel neurodevelopmental disorder caused by variants in the zinc finger protein 292 gene (ZNF292). Methods: We ascertained a cohort of 28 families with ID due to putatively pathogenic ZNF292 variants that were identified via targeted and exome sequencing. Available data were analyzed to characterize the canonical phenotype and examine genotype–phenotype relationships. Results: Probands presented with ID as well as a spectrum of neurodevelopmental features including ASD, among others. All ZNF292 variants were de novo, except in one family with dominant inheritance. ZNF292 encodes a highly conserved zinc finger protein that acts as a transcription factor and is highly expressed in the developing human brain supporting its critical role in neurodevelopment. Conclusion: De novo and dominantly inherited variants in ZNF292 are associated with a range of neurodevelopmental features including ID and ASD. The clinical spectrum is broad, and most individuals present with mild to moderate ID with or without other syndromic features. Our results suggest that variants in ZNF292 are likely a recurrent cause of a neurodevelopmental disorder manifesting as ID with or without ASD.
CRIS-Team Scopus Importer:2019-11-26
Keywords: autism spectrum disorders; exome sequencing; intellectual disability; next-generation sequencing; ZNF292

De novo missense mutations in the NAA10 gene cause severe non-syndromic developmental delay in males and females - Popp, Bernt; Stove, Svein I.; Endele, Sabine; Myklebust, Line M.; Hoyer, Juliane; Sticht, Heinrich; Azzarello-Burri, Silvia; Rauch, Anita; Arnesen, Thomas; Reis, André (European journal of human genetics, 2015)
Recent studies revealed the power of whole-exome sequencing to identify mutations in sporadic cases with non-syndromic intellectual disability. We now identified de novo missense variants in NAA10 in two unrelated individuals, a boy and a girl, with severe global developmental delay but without any major dysmorphism by trio whole-exome sequencing. Both de novo variants were predicted to be deleterious, and we excluded other variants in this gene. This X-linked gene encodes N-alpha-acetyltransferase 10, the catalytic subunit of the NatA complex involved in multiple cellular processes. A single hypomorphic missense variant p.(Ser37Pro) was previously associated with Ogden syndrome in eight affected males from two different families. This rare disorder is characterized by a highly recognizable phenotype, global developmental delay and results in death during infancy. In an attempt to explain the discrepant phenotype, we used in vitro N-terminal acetylation assays which suggested that the severity of the phenotype correlates with the remaining catalytic activity. The variant in the Ogden syndrome patients exhibited a lower activity than the one seen in the boy with intellectual disability, while the variant in the girl was the most severe exhibiting only residual activity in the acetylation assays used. We propose that N-terminal acetyltransferase deficiency is clinically heterogeneous with the overall catalytic activity determining the phenotypic severity.
EVALuna2:9247

De novo missense variants in FBXO11 alter its protein expression and subcellular localization - Gregor, Anne; Meerbrei, Tanja; Gerstner, Thorsten; Toutain, Annick; Lynch, Sally Ann; Stals, Karen; Maxton, Caroline; Lemke, Johannes R.; Bernat, John A.; Bombei, Hannah M.; Foulds, Nicola; Hunt, David; et al. (Human Molecular Genetics, 2022)
Recently, others and we identified de novo FBXO11 (F-Box only protein 11) variants as causative for a variable neurodevelopmental disorder (NDD). We now assembled clinical and mutational information on 23 additional individuals. The phenotypic spectrum remains highly variable, with developmental delay and/or intellectual disability as the core feature and behavioral anomalies, hypotonia and various facial dysmorphism as frequent aspects. The mutational spectrum includes intragenic deletions, likely gene disrupting and missense variants distributed across the protein. To further characterize the functional consequences of FBXO11 missense variants, we analyzed their effects on protein expression and localization by overexpression of 17 different mutant constructs in HEK293 and HeLa cells. We found that the majority of missense variants resulted in subcellular mislocalization and/or reduced FBXO11 protein expression levels. For instance, variants located in the nuclear localization signal and the N-terminal F-Box domain lead to altered subcellular localization with exclusion from the nucleus or the formation of cytoplasmic aggregates and to reduced protein levels in western blot. In contrast, variants localized in the C-terminal Zn-finger UBR domain lead to an accumulation in the cytoplasm without alteration of protein levels. Together with the mutational data, our functional results suggest that most missense variants likely lead to a loss of the original FBXO11 function and thereby highlight haploinsufficiency as the most likely disease mechanism for FBXO11-associated NDDs.
CRIS-Team Scopus Importer:2022-03-04

Detecting tandem repeat variants in coding regions using code-adVNTR - Park, Jonghun; Bakhtiari, Mehrdad; Popp, Bernt; Wiesener, Michael; Bafna, Vineet (iScience, 2022)
The human genome contains more than one million tandem repeats (TRs), DNA sequences containing multiple approximate copies of a motif repeated contiguously. TRs account for significant genetic variation, with 50 + diseases attributed to changes in motif number. A few diseases have been to be caused by small indels in variable number tandem repeats (VNTRs) including poly-cystic kidney disease type 1 (MCKD1) and monogenic type 1 diabetes. However, small indels in VNTRs are largely unexplored mainly due to the long and complex structure of VNTRs with multiple motifs. We developed a method, code-adVNTR, that utilizes multi-motif hidden Markov models to detect both, motif count variation and small indels, within VNTRs. In simulated data, code-adVNTR outperformed GATK-HaplotypeCaller in calling small indels within large VNTRs. We used code-adVNTR to characterize coding VNTRs in the 1000 genomes data identifying many population-specific variants, and to reliably call MUC1 mutations for MCKD1.
CRIS-Team Scopus Importer:2022-11-18
Keywords: Genetics; Genomics; Human genetics; Molecular genetics

Differential Coassembly of α1-GABAARs Associated with Epileptic Encephalopathy - Hannan, Saad; Affandi, Aida H. B.; Minere, Marielle; Jones, Charlotte; Goh, Pollyanna; Warnes, Gary; Popp, Bernt; Trollmann, Regina; Nizetic, Dean; Smart, Trevor G. (The Journal of Neuroscience, 2020)
GABAA receptors (GABAARs) are profoundly important for controlling neuronal excitability. Spontaneous and familial mutations to these receptors feature prominently in excitability disorders and neurodevelopmental deficits following disruption to GABA-mediated inhibition. Recent genotyping of an individual with severe epilepsy and Williams-Beuren syndrome identified a frameshifting de novo variant in a major GABAAR gene, GABRA1 This truncated the α1 subunit between the third and fourth transmembrane domains and introduced 24 new residues forming the mature protein, α1Lys374Serfs*25 Cell surface expression of mutant murine GABAARs is severely impaired compared with WT, due to retention in the endoplasmic reticulum. Mutant receptors were differentially coexpressed with β3, but not with β2, subunits in mammalian cells. Reduced surface expression was reflected by smaller IPSCs, which may underlie the induction of seizures. The mutant does not have a dominant-negative effect on native neuronal GABAAR expression since GABA current density was unaffected in hippocampal neurons, although mutant receptors exhibited limited GABA sensitivity. To date, the underlying mechanism is unique for epileptogenic variants and involves differential β subunit expression of GABAAR populations, which profoundly affected receptor function and synaptic inhibition.SIGNIFICANCE STATEMENT GABAARs are critical for controlling neural network excitability. They are ubiquitously distributed throughout the brain, and their dysfunction underlies many neurologic disorders, especially epilepsy. Here we report the characterization of an α1-GABAAR variant that results in severe epilepsy. The underlying mechanism is structurally unusual, with the loss of part of the α1 subunit transmembrane domain and part-replacement with nonsense residues. This led to compromised and differential α1 subunit cell surface expression with β subunits resulting in severely reduced synaptic inhibition. Our study reveals that disease-inducing variants can affect GABAAR structure, and consequently subunit assembly and cell surface expression, critically impacting on the efficacy of synaptic inhibition, a property that will orchestrate the extent and duration of neuronal excitability.
CRIS-Team Scopus Importer:2020-07-31
Keywords: epilepsy; GABA-A receptor; inhibition; synaptic transmission; α subunit variant

Discovering a new part of the phenotypic spectrum of Coffin-Siris syndrome in a fetal cohort - van der Sluijs, Pleuntje J.; Joosten, Marieke; Alby, Caroline; Attié-Bitach, Tania; Gilmore, Kelly; Dubourg, Christele; Fradin, Mélanie; Wang, Tianyun; Kurtz-Nelson, Evangeline C.; Ahlers, Kaitlyn P.; Arts, Peer; Barnett, Christopher P.; et al. (Genetics in Medicine, 2022)
Purpose: Genome-wide sequencing is increasingly being performed during pregnancy to identify the genetic cause of congenital anomalies. The interpretation of prenatally identified variants can be challenging and is hampered by our often limited knowledge of prenatal phenotypes. To better delineate the prenatal phenotype of Coffin-Siris syndrome (CSS), we collected clinical data from patients with a prenatal phenotype and a pathogenic variant in one of the CSS-associated genes. Methods: Clinical data was collected through an extensive web-based survey. Results: We included 44 patients with a variant in a CSS-associated gene and a prenatal phenotype; 9 of these patients have been reported before. Prenatal anomalies that were frequently observed in our cohort include hydrocephalus, agenesis of the corpus callosum, hypoplastic left heart syndrome, persistent left vena cava, diaphragmatic hernia, renal agenesis, and intrauterine growth restriction. Anal anomalies were frequently identified after birth in patients with ARID1A variants (6/14, 43%). Interestingly, pathogenic ARID1A variants were much more frequently identified in the current prenatal cohort (16/44, 36%) than in postnatal CSS cohorts (5%-9%). Conclusion: Our data shed new light on the prenatal phenotype of patients with pathogenic variants in CSS genes.
CRIS-Team Scopus Importer:2022-06-03
Keywords: ARID1A; ARID1B BAFopathy; BAF-complex; Fetal; SMARCA4; SMARCB1

Dissecting TSC2-mutated renal and hepatic angiomyolipomas in an individual with ARID1B-associated intellectual disability - Popp, Bernt; Agaimy, Abbas; Kraus, Cornelia; Knaup, Karl; Ekici, Arif Bülent; Uebe, Steffen; Reis, André; Wiesener, Michael; Zweier, Christiane (BMC Cancer, 2019)
Background: Several subunits of the SWI/SNF chromatin remodeling complex are implicated in both cancer and neurodevelopmental disorders (NDD). Though there is no clinical evidence for an increased tumor risk in individuals with NDDs due to germline mutations in most of these genes so far, this has been repeatedly proposed and discussed. A young woman with NDD due to a de novo mutation in ARID1B now presented with a large renal (> 19 cm in diameter) and multiple hepatic angiomyolipomas (AMLs) but no other signs of tuberous sclerosis complex. Methods: We analyzed tumor and healthy tissue samples with exome and panel sequencing. Results: Additionally to the previously known, germline ARID1B variant we identified a post-zygotic truncating TSC2 variant in both renal and hepatic AMLs but not in any of the healthy tissues. We did not detect any further, obvious tumor driver events. The identification of a passenger variant in SIPA1L3 in both AMLs points to a common clonal origin. Metastasis of the renal AML into the liver is unlikely on the basis of discordant histopathological features. Our findings therefore point to very low-grade mosaicism for the TSC2 variant, possibly in a yet unknown mesenchymal precursor cell that expanded clonally during tumor development. A possible contribution of the germline ARID1B variant to the tumorigenesis remains unclear but cannot be excluded given the absence of any other evident tumor drivers in the AMLs. Conclusion: This unique case highlights the blurred line between tumor genetics and post-zygotic events that can complicate exact molecular diagnoses in patients with rare manifestations. It also demonstrates the relevance of multiple disorders in a single individual, the challenges of detecting low-grade mosaicisms, and the importance of proper diagnosis for treatment and surveillance.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Angiomyolipoma; ARID1B; Mosaic; Neurodevelopmental disorders; TSC2; Tuberous sclerosis complex

Diverse molecular causes of unsolved autosomal dominant tubulointerstitial kidney diseases - Wopperer, Florian; Knaup, Karl; Stanzick, Kira J.; Schneider, Karen; Jobst-Schwan, Tilman; Ekici, Arif Bülent; Uebe, Steffen; Wenzel, Andrea; Schliep, Stefan; Schürfeld, Carsten; Seitz, Randolf; Bernhardt, Wanja; et al. (Kidney International, 2022)
Autosomal Dominant Tubulointerstitial Kidney Disease (ADTKD) is caused by mutations in one of at least five genes and leads to kidney failure usually in mid adulthood. Throughout the literature, variable numbers of families have been reported, where no mutation can be found and therefore termed ADTKD-not otherwise specified. Here, we aim to clarify the genetic cause of their diseases in our ADTKD registry. Sequencing for all known ADTKD genes was performed, followed by SNaPshot minisequencing for the dupC (an additional cytosine within a stretch of seven cytosines) mutation of MUC1. A virtual panel containing 560 genes reported in the context of kidney disease (nephrome) and exome sequencing were then analyzed sequentially. Variants were validated and tested for segregation. In 29 of the 45 registry families, mutations in known ADTKD genes were found, mostly in MUC1. Sixteen families could then be termed ADTKD-not otherwise specified, of which nine showed diagnostic variants in the nephrome (four in COL4A5, two in INF2 and one each in COL4A4, PAX2, SALL1 and PKD2). In the other seven families, exome sequencing analysis yielded potential disease associated variants in novel candidate genes for ADTKD; evaluated by database analyses and genome-wide association studies. For the great majority of our ADTKD registry we were able to reach a molecular genetic diagnosis. However, a small number of families are indeed affected by diseases classically described as a glomerular entity. Thus, incomplete clinical phenotyping and atypical clinical presentation may have led to the classification of ADTKD. The identified novel candidate genes by exome sequencing will require further functional validation.
CRIS-Team Scopus Importer:2022-07-15
Keywords: ADTKD; Alport syndrome; exome; MITKD; MUC1; UMOD

DLG4-related synaptopathy: a new rare brain disorder - Rodriguez-Palmero, Agusti; Boerrigter, Melissa Maria; Gomez-Andres, David; Aldinger, Kimberly A.; Marcos-Alcalde, Inigo; Popp, Bernt; Everman, David B.; Lovgren, Alysia Kern; Arpin, Stephanie; Bahrambeigi, Vahid; Beunders, Gea; Bisgaard, Anne-Marie; et al. (Genetics in Medicine, 2021)
Purpose: Postsynaptic density protein-95 (PSD-95), encoded by DLG4, regulates excitatory synaptic function in the brain. Here we present the clinical and genetic features of 53 patients (42 previously unpublished) with DLG4 variants. Methods: The clinical and genetic information were collected through GeneMatcher collaboration. All the individuals were investigated by local clinicians and the gene variants were identified by clinical exome/genome sequencing. Results: The clinical picture was predominated by early onset global developmental delay, intellectual disability, autism spectrum disorder, and attention deficit–hyperactivity disorder, all of which point to a brain disorder. Marfanoid habitus, which was previously suggested to be a characteristic feature of DLG4-related phenotypes, was found in only nine individuals and despite some overlapping features, a distinct facial dysmorphism could not be established. Of the 45 different DLG4 variants, 39 were predicted to lead to loss of protein function and the majority occurred de novo (four with unknown origin). The six missense variants identified were suggested to lead to structural or functional changes by protein modeling studies. Conclusion: The present study shows that clinical manifestations associated with DLG4 overlap with those found in other neurodevelopmental disorders of synaptic dysfunction; thus, we designate this group of disorders as DLG4-related synaptopathy. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2021-03-05

Do the exome: A case of Williams-Beuren syndrome with severe epilepsy due to a truncating de novo variant in GABRA1 - Popp, Bernt; Trollmann, Regina; Büttner, Christian; Caliebe, Almuth; Thiel, Christian; Hüffmeier, Ulrike; Reis, André; Zweier, Christiane (European Journal of Medical Genetics, 2016)
Williams-Beuren syndrome (WBS) is a relatively common, clinically recognizable microdeletion syndrome. In most cases the typical heterozygous deletion of 1.5 Mb on chromosome 7q11.23 spanning about 26 genes can be identified. Also some larger or smaller atypical deletions have been reported and associated with additional or atypical phenotypic aspects. We report on an individual with typical WBS due to the common deletion and with refractory infantile spasms. Using trio-exome sequencing, we identified a de novo truncating variant c.1200del, p (Lys401Serfs*25) in GABRA1 as the likely cause of the early onset epilepsy. This unique case not only allows to further define the phenotypic spectrum of infantile epileptic encephalopathy associated with rare de novo GABRA1 variants but exemplifies the need for a sensitive review of unclear associations in clinically defined syndromes and for extended diagnostic work-up in individuals with unusual presentations of a genetically confirmed diagnosis.
EVALuna2:9310

Evolutionary conserved networks of human height identify multiple Mendelian causes of short stature - Hauer, Nadine; Popp, Bernt; Taher, Leila; Vogl, Carina; Dhandapany, Perundurai S.; Büttner, Christian; Uebe, Steffen; Sticht, Heinrich; Ferrazzi, Fulvia; Ekici, Arif Bülent; De Luca, Alessandro; Klinger, Patricia; et al. (European journal of human genetics, 2019)
Height is a heritable and highly heterogeneous trait. Short stature affects 3% of the population and in most cases is genetic in origin. After excluding known causes, 67% of affected individuals remain without diagnosis. To identify novel candidate genes for short stature, we performed exome sequencing in 254 unrelated families with short stature of unknown cause and identified variants in 63 candidate genes in 92 (36%) independent families. Based on systematic characterization of variants and functional analysis including expression in chondrocytes, we classified 13 genes as strong candidates. Whereas variants in at least two families were detected for all 13 candidates, two genes had variants in 6 (UBR4) and 8 (LAMA5) families, respectively. To facilitate their characterization, we established a clustered network of 1025 known growth and short stature genes, which yielded 29 significantly enriched clusters, including skeletal system development, appendage development, metabolic processes, and ciliopathy. Eleven of the candidate genes mapped to 21 of these clusters, including CPZ, EDEM3, FBRS, IFT81, KCND1, PLXNA3, RASA3, SLC7A8, UBR4, USP45, and ZFHX3. Fifty additional growth-related candidates we identified await confirmation in other affected families. Our study identifies Mendelian forms of growth retardation as an important component of idiopathic short stature.
CRIS-Team Scopus Importer:2019-05-24

Exome Pool-Seq in neurodevelopmental disorders - Popp, Bernt; Ekici, Arif Bülent; Thiel, Christian; Hoyer, Juliane; Wiesener, Antje; Kraus, Cornelia; Reis, André; Zweier, Christiane (European journal of human genetics, 2017)
High throughput sequencing has greatly advanced disease gene identification, especially in heterogeneous entities. Despite falling costs this is still an expensive and laborious technique, particularly when studying large cohorts. To address this problem we applied Exome Pool-Seq as an economic and fast screening technology in neurodevelopmental disorders (NDDs). Sequencing of 96 individuals can be performed in eight pools of 12 samples on less than one Illumina sequencer lane. In a pilot study with 96 cases we identified 27 variants, likely or possibly affecting function. Twenty five of these were identified in 923 established NDD genes (based on SysID database, status November 2016) (ACTB, AHDC1, ANKRD11, ATP6V1B2, ATRX, CASK, CHD8, GNAS, IFIH1, KCNQ2, KMT2A, KRAS, MAOA, MED12, MED13L, RIT1, SETD5, SIN3A, TCF4, TRAPPC11, TUBA1A, WAC, ZBTB18, ZMYND11), two in 543 (SysID) candidate genes (ZNF292, BPTF), and additionally a de novo loss-of-function variant in LRRC7, not previously implicated in NDDs. Most of them were confirmed to be de novo, but we also identified X-linked or autosomal-dominantly or autosomal-recessively inherited variants. With a detection rate of 28%, Exome Pool-Seq achieves comparable results to individual exome analyses but reduces costs by >85%. Compared with other large scale approaches using Molecular Inversion Probes (MIP) or gene panels, it allows flexible re-analysis of data. Exome Pool-Seq is thus well suited for large-scale, cost-efficient and flexible screening in characterized but heterogeneous entities like NDDs.
EVALuna2:9387

Expanding the clinical and molecular spectrum of the novel CYFIP2-related neurodevelopmental disorder and functional proof of aberrant WRC-mediated actin dynamics - Begemann, A.; Sticht, Heinrich; Mcwalter, K.; Vitobello, A.; Faivre, L.; Alhaddad, B.; Banka, S.; Becker, J.; Bierhals, T.; Brown, K.; Bruel, A.; Brunet, T.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Expanding the Phenotype Associated with NAA10-Related N-Terminal Acetylation Deficiency - Saunier, Chloe; Stove, Svein Isungset; Popp, Bernt; Gerard, Benedicte; Blenski, Marina; Ahmew, Nicholas; De Bie, Charlotte; Goldenberg, Paula; Isidor, Bertrand; Keren, Boris; Leheup, Bruno; Lampert, Laetitia; et al. (Human Mutation, 2016)
N-terminal acetylation is a common protein modification in eukaryotes associated with numerous cellular processes. Inherited mutations in NAA10, encoding the catalytic subunit of the major N-terminal acetylation complex NatA have been associated with diverse, syndromic X-linked recessive disorders, whereas de novo missense mutations have been reported in one male and one female individual with severe intellectual disability but otherwise unspecific phenotypes. Thus, the full genetic and clinical spectrum of NAA10 deficiency is yet to be delineated. We identified three different novel and one known missense mutation in NAA10, de novo in 11 females, and due to maternal germ line mosaicism in another girl and her more severely affected and deceased brother. In vitro enzymatic assays for the novel, recurrent mutations p.(Arg83Cys) and p.(Phe128Leu) revealed reduced catalytic activity. X-inactivation was random in five females. The core phenotype of X-linked NAA10-related N-terminal-acetyltransferase deficiency in both males and females includes developmental delay, severe intellectual disability, postnatal growth failure with severe microcephaly, and skeletal or cardiac anomalies. Genotype-phenotype correlations within and between both genders are complex and may include various factors such as location and nature of mutations, enzymatic stability and activity, and X-inactivation in females.
EVALuna2:9314

Exploring the phenotypical spectrum of BRD4 defects - Hauer, Nadine; Vogl, C.; Popp, Bernt; Buettner, C.; Uebe, S.; Sticht, Heinrich; Ekici, Arif Bülent; Klinger, Patricia; Kraus, Cornelia; Krumbiegel, M.; Wiesener, A.; Dörr, Helmuth-Günther; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Genetic and phenotypic spectrum associated with IFIH1 gain-of-function - Rice, Gillian; Park, Sehoon; Gavazzi, Francesco; Adang, Laura A.; Ayuk, Loveline A.; Van Eyck, Lien; Seabra, Luis; Barrea, Christophe; Battini, Roberta; Belot, Alexandre; Berg, Stefan; De Villemeur, Thierry Billette; et al. (Human Mutation, 2020)
IFIH1 gain-of-function has been reported as a cause of a type I interferonopathy encompassing a spectrum of autoinflammatory phenotypes including Aicardi-Goutieres syndrome and Singleton Merten syndrome. Ascertaining patients through a European and North American collaboration, we set out to describe the molecular, clinical and interferon status of a cohort of individuals with pathogenic heterozygous mutations in IFIH1. We identified 74 individuals from 51 families segregating a total of 27 likely pathogenic mutations in IFIH1. Ten adult individuals, 13.5% of all mutation carriers, were clinically asymptomatic (with seven of these aged over 50 years). All mutations were associated with enhanced type I interferon signaling, including six variants (22%) which were predicted as benign according to multiple in silico pathogenicity programs. The identified mutations cluster close to the ATP binding region of the protein. These data confirm variable expression and nonpenetrance as important characteristics of the IFIH1 genotype, a consistent association with enhanced type I interferon signaling, and a common mutational mechanism involving increased RNA binding affinity or decreased efficiency of ATP hydrolysis and filament disassembly rate.
CRIS-Team WoS Importer:2020-01-28

Haploinsufficiency of the Chromatin Remodeler BPTF Causes Syndromic Developmental and Speech Delay, Postnatal Microcephaly, and Dysmorphic Features - Stankiewicz, Pawel; Khan, Tahir N.; Szafranski, Przemyslaw; Slattery, Leah; Streff, Haley; Vetrini, Francesco; Bernstein, Jonathan A.; Brown, Chester W.; Rosenfeld, Jill A.; Rednam, Surya; Scollon, Sarah; Bergstrom, Katie L.; et al. (American Journal of Human Genetics, 2017)
Bromodomain PHD finger transcription factor (BPTF) is the largest subunit of nucleosome remodeling factor (NURF), a member of the ISWI chromatin-remodeling complex. However, the clinical consequences of disruption of this complex remain largely uncharacterized. BPTF is required for anterior-posterior axis formation of the mouse embryo and was shown to promote posterior neuroectodermal fate by enhancing Smad2-activated wnt8 expression in zebrafish. Here, we report eight loss-of-function and two missense variants (eight de novo and two of unknown origin) in BPTF on 17q24.2. The BPTF variants were found in unrelated individuals aged between 2.1 and 13 years, who manifest variable degrees of developmental delay/intellectual disability (10/10), speech delay (10/10), postnatal microcephaly (7/9), and dysmorphic features (9/10). Using CRISPR-Cas9 genome editing of bptf in zebrafish to induce a loss of gene function, we observed a significant reduction in head size of F0 mutants compared to control larvae. Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) and phospho-histone H3 (PH3) staining to assess apoptosis and cell proliferation, respectively, showed a significant increase in cell death in F0 mutants compared to controls. Additionally, we observed a substantial increase of the ceratohyal angle of the craniofacial skeleton in bptf F0 mutants, indicating abnormal craniofacial patterning. Taken together, our data demonstrate the pathogenic role of BPTF haploinsufficiency in syndromic neurodevelopmental anomalies and extend the clinical spectrum of human disorders caused by ablation of chromatin remodeling complexes.
EVALuna2:9361

Identification of novel candidate genes for idiopathic short stature using whole exome sequencing - Thiel, Christian; Hauer, Nadine; Vogl, C.; Ahmadian, R.; Dhandapany, P. S.; Popp, Bernt; Buettner, C.; Ube, S.; Sticht, Heinrich; Ferrazzi, Fulvia; Ekici, Arif Bülent; De Luca, A.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Intrafamilial neurological phenotypic variability due to either biallelic or monoallelic pathogenic variants in CACNA1A - Mammadova, Dilbar; Kraus, Cornelia; Leis, Thomas; Popp, Bernt; Zweier, Christiane; Reis, André; Trollmann, Regina (Frontiers in Neurology, 2024)
Pathogenic heterozygous variants in CACNA1A are associated with familial hemiplegic migraine, episodic ataxia type 2 and spinocerebellar ataxia type 6, and more recently, neurodevelopmental disorders. We describe a severe, early-onset phenotype including severe muscular hypotonia, early-onset epileptic seizures, apnoea, optic atrophy and dysphagia in three siblings carrying compound heterozygous frameshift variants in CACNA1A. Two male patients died at the age of 5 or 14 months of suspected SIDS or severe developmental epileptic encephalopathy (DEE) with refractory seizures and apnoea. A male child (index patient) developed severe early-onset DEE including seizures and ictal apnoea at the age of 4 weeks. Another male child developed generalized epilepsy and mild intellectual impairment in late infancy, and his mother and his maternal uncle were identified as carriers of a known CACNA1A pathogenic variant [c.2602delG heterozygous, p. (Ala868Profs*24)] with a diagnosis of episodic ataxia type 2. This maternal pathogenic variant c.2602delG was detected in the index patient and child 2. Trio-Exome sequencing identified an additional heterozygous pathogenic variant in the CACNA1A gene, c.5476delC, p.(His1826Thrfs*30) in the index patient and child 2, which was inherited from the asymptomatic father. In conclusion, the novel compound heterozygosity for two frameshift pathogenic variants, maternally [c.2602delG, p.(Ala868Profs*24)] and paternally [c.5476delC, p.(His1826Thrfs*3)] is associated with a severe phenotype of early-onset DEE. This observation highlights the necessity of additional analyses to clarify unusual phenotypes even if a pathogenic variant has already been identified, and expands the clinical spectrum of CACNA1A-related disorders.
CRIS-Team Scopus Importer:2024-10-25
Keywords: apneic spells; burst suppression; developmental epileptic encephalopathy; early-onset epileptic encephalopathy; generalized epilepsy; optic nerve atrophy

Is MED13L-related intellectual disability a recognizable syndrome? - Tørring, Pernille Mathiesen; Larsen, Martin Jakob; Brasch-Andersen, Charlotte; Krogh, Lotte Nylandsted; Kibæk, Maria; Laulund, Lone; Illum, Niels; Dunkhase-Heinl, Ulrike; Wiesener, Antje; Popp, Bernt; Marangi, Giuseppe; Hjortshøj, Tina Duelund; et al. (European Journal of Medical Genetics, 2018)
INTRODUCTION: MED13L-related intellectual disability is characterized by moderate intellectual disability (ID), speech impairment, and dysmorphic facial features. We present 8 patients with MED13L-related intellectual disability and review the literature for phenotypical and genetic aspects of previously described patients. MATERIALS AND METHODS: In the search for genetic aberrations in individuals with ID, two of the patients were identified by chromosomal microarray analysis, and five by exome sequencing. One of the individuals, suspected of MED13L-related intellectual disability, based on clinical features, was identified by Sanger sequencing. RESULTS: All 8 individuals had de novo MED13L aberrations, including two intragenic microdeletions, two frameshift, three nonsense variants, and one missense variant. Phenotypically, they all had intellectual disability, speech and motor delay, and features of the mouth (open mouth appearance, macroglossia, and/or macrostomia). Two individuals were diagnosed with autism, and one had autistic features. One had complex congenital heart defect, and one had persistent foramen ovale. The literature was reviewed with respect to clinical and dysmorphic features, and genetic aberrations. CONCLUSIONS: Even if most clinical features of MED13L-related intellectual disability are rather non-specific, the syndrome may be suspected in some individuals based on the association of developmental delay, speech impairment, bulbous nasal tip, and macroglossia, macrostomia, or open mouth appearance.
EVALuna2:34847

Mutations in MBOAT7, Encoding Lysophosphatidylinositol Acyltransferase I, Lead to Intellectual Disability Accompanied by Epilepsy and Autistic Features - Johansen, Anide; Rosti, Rasim O.; Musaev, Damir; Sticca, Evan; Harripaul, Ricardo; Zaki, Maha; Caglayan, Ahmet Okay; Azam, Matloob; Sultan, Tipu; Froukh, Tawfiq; Reis, André; Popp, Bernt; et al. (American Journal of Human Genetics, 2016)
The risk of epilepsy among individuals with intellectual disability (ID) is approximately ten times that of the general population. From a cohort of >5,000 families affected by neurodevelopmental disorders, we identified six consanguineous families harboring homozygous inactivating variants in MBOAT7, encoding lysophosphatidylinositol acyltransferase (LPIAT1). Subjects presented with ID frequently accompanied by epilepsy and autistic features. LPIAT1 is a membrane-bound phospholipid-remodeling enzyme that transfers arachidonic acid (AA) to lysophosphatidylinositol to produce AA-containing phosphatidylinositol. This study suggests a role for AA-containing phosphatidylinositols in the development of ID accompanied by epilepsy and autistic features.
EVALuna2:9331

Mutations in the BAF-Complex Subunit DPF2 Are Associated with Coffin-Siris Syndrome - Vasileiou, Georgia; Vergarajauregui, Silvia; Endele, Sabine; Popp, Bernt; Büttner, Christian; Ekici, Arif Bülent; Gerard, Marion; Bramswig, Nuria C.; Albrecht, Beate; Clayton-Smith, Jill; Morton, Jenny; Tomkins, Susan; et al. (American Journal of Human Genetics, 2018)
Variants affecting the function of different subunits of the BAF chromatin-remodelling complex lead to various neurodevelopmental syndromes, including Coffin-Siris syndrome. Furthermore, variants in proteins containing PHD fingers, motifs recognizing specific histone tail modifications, have been associated with several neurological and developmental-delay disorders. Here, we report eight heterozygous de novo variants (one frameshift, two splice site, and five missense) in the gene encoding the BAF complex subunit double plant homeodomain finger 2 (DPF2). Affected individuals share common clinical features described in individuals with Coffin-Siris syndrome, including coarse facial features, global developmental delay, intellectual disability, speech impairment, and hypoplasia of fingernails and toenails. All variants occur within the highly conserved PHD1 and PHD2 motifs. Moreover, missense variants are situated close to zinc binding sites and are predicted to disrupt these sites. Pull-down assays of recombinant proteins and histone peptides revealed that a subset of the identified missense variants abolish or impaire DPF2 binding to unmodified and modified H3 histone tails. These results suggest an impairment of PHD finger structural integrity and cohesion and most likely an aberrant recognition of histone modifications. Furthermore, the overexpression of these variants in HEK293 and COS7 cell lines was associated with the formation of nuclear aggregates and the recruitment of both wild-type DPF2 and BRG1 to these aggregates. Expression analysis of truncating variants found in the affected individuals indicated that the aberrant transcripts escape nonsense-mediated decay. Altogether, we provide compelling evidence that de novo variants in DPF2 cause Coffin-Siris syndrome and propose a dominant-negative mechanism of pathogenicity.

Mutations in the BAF-complex subunit DPF2 are associated with Coffin-Siris syndrome - Vasileiou, G.; Vergarajauregui, S.; Endele, Sabine; Popp, Bernt; Büttner, Christian; Ekici, Arif Bülent; Gerard, M.; Bramswig, N. C.; Albrecht, B.; Clayton-Smith, J.; Morton, J.; Tomkins, S.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Need for high-resolution Genetic Analysis in iPSC: Results and Lessons from the ForIPS Consortium - Popp, Bernt; Krumbiegel, Mandy; Grosch, Janina; Sommer, Annika; Uebe, Steffen; Kohl, Zacharias; Ploetz, Sonja; Farrell, Michaela; Trautmann, Udo; Kraus, Cornelia; Ekici, Arif Bülent; Asadollahi, Reza; et al. (Scientific Reports, 2018)
Genetic integrity of induced pluripotent stem cells (iPSCs) is essential for their validity as disease models and for potential therapeutic use. We describe the comprehensive analysis in the ForIPS consortium: an iPSC collection from donors with neurological diseases and healthy controls. Characterization included pluripotency confirmation, fingerprinting, conventional and molecular karyotyping in all lines. In the majority, somatic copy number variants (CNVs) were identified. A subset with available matched donor DNA was selected for comparative exome sequencing. We identified single nucleotide variants (SNVs) at different allelic frequencies in each clone with high variability in mutational load. Low frequencies of variants in parental fibroblasts highlight the importance of germline samples. Somatic variant number was independent from reprogramming, cell type and passage. Comparison with disease genes and prediction scores suggest biological relevance for some variants. We show that high-throughput sequencing has value beyond SNV detection and the requirement to individually evaluate each clone.
EVALuna2:34839

New insights into the clinical and molecular spectrum of the novel CYFIP2-related neurodevelopmental disorder and impairment of the WRC-mediated actin dynamics - Begemann, Anaïs; Sticht, Heinrich; Begtrup, Amber; Vitobello, Antonio; Faivre, Laurence; Banka, Siddharth; Alhaddad, Bader; Asadollahi, Reza; Becker, Jessica; Bierhals, Tatjana; Brown, Kathleen E.; Bruel, Ange Line; et al. (Genetics in Medicine, 2020)
Purpose: A few de novo missense variants in the cytoplasmic FMRP-interacting protein 2 (CYFIP2) gene have recently been described as a novel cause of severe intellectual disability, seizures, and hypotonia in 18 individuals, with p.Arg87 substitutions in the majority. Methods: We assembled data from 19 newly identified and all 18 previously published individuals with CYFIP2 variants. By structural modeling and investigation of WAVE-regulatory complex (WRC)-mediated actin polymerization in six patient fibroblast lines we assessed the impact of CYFIP2 variants on the WRC. Results: Sixteen of 19 individuals harbor two previously described and 11 novel (likely) disease-associated missense variants. We report p.Asp724 as second mutational hotspot (4/19 cases). Genotype–phenotype correlation confirms a consistently severe phenotype in p.Arg87 patients but a more variable phenotype in p.Asp724 and other substitutions. Three individuals with milder phenotypes carry putative loss-of-function variants, which remain of unclear pathogenicity. Structural modeling predicted missense variants to disturb interactions within the WRC or impair CYFIP2 stability. Consistent with its role in WRC-mediated actin polymerization we substantiate aberrant regulation of the actin cytoskeleton in patient fibroblasts. Conclusion: Our study expands the clinical and molecular spectrum of CYFIP2-related neurodevelopmental disorder and provides evidence for aberrant WRC-mediated actin dynamics as contributing cellular pathomechanism.
CRIS-Team Scopus Importer:2020-11-13
Keywords: CYFIP2; epilepsy; intellectual disability; WASF; WAVE-regulatory complex (WRC)

Prenatal diagnosis of HNF1B-associated renal cysts: Is there a need to differentiate intragenic variants from 17q12 microdeletion syndrome? - Vasileiou, Georgia; Hoyer, Juliane; Thiel, Christian; Schaefer, Jan Thomas; Zapke, Maren; Krumbiegel, Mandy; Kraus, Cornelia; Zweier, Markus; Uebe, Steffen; Ekici, Arif Bülent; Schneider, Michael; Wiesener, Michael; et al. (Prenatal Diagnosis, 2019)
Objective 17q12 microdeletions containing HNF1B and intragenic variants within this gene are associated with variable developmental, endocrine, and renal anomalies, often already noted prenatally as hyperechogenic/cystic kidneys. Here, we describe prenatal and postnatal phenotypes of seven individuals with HNF1B aberrations and compare their clinical and genetic data to those of previous studies. Methods Prenatal sequencing and postnatal chromosomal microarray analysis were performed in seven individuals with renal and/or neurodevelopmental phenotypes. We evaluated HNF1B-related clinical features from 82 studies and reclassified 192 reported intragenic HNF1B variants. Results In a prenatal case, we identified a novel in-frame deletion p.(Gly239del) within the HNF1B DNA-binding domain, a mutational hot spot as demonstrated by spatial clustering analysis and high computational prediction scores. The six postnatally diagnosed individuals harbored 17q12 microdeletions. Literature screening revealed variable reporting of HNF1B-associated clinical traits. Overall, both mutation groups showed a high phenotypic heterogeneity. The reclassification of all previously reported intragenic HNF1B variants provided an up-to-date overview of the mutational spectrum. Conclusions We highlight the value of prenatal HNF1B screening in renal developmental diseases. Standardized clinical reporting and systematic classification of HNF1B variants are necessary for a more accurate risk quantification of prenatal and postnatal clinical features, improving genetic counseling and prenatal decision making.
CRIS-Team WoS Importer:2019-11-08

Prevalence of hereditary tubulointerstitial kidney diseases in the German Chronic Kidney Disease study - Popp, Bernt; Ekici, Arif Bülent; Knaup, Karl; Schneider, Karen; Uebe, Steffen; Park, Jonghun; Bafna, Vineet; Meiselbach, Heike; Eckardt, Kai-Uwe; Schiffer, Mario; Wiesmann da Silva Reis, André; Kraus, Cornelia; et al. (European Journal of Human Genetics, 2022)
Hereditary chronic kidney disease (CKD) appears to be more frequent than the clinical perception. Exome sequencing (ES) studies in CKD cohorts could identify pathogenic variants in similar to 10% of individuals. Tubulointerstitial kidney diseases, showing no typical clinical/histologic finding but tubulointerstitial fibrosis, are particularly difficult to diagnose. We used a targeted panel (29 genes) and MUC1-SNaPshot to sequence 271 DNAs, selected in defined disease entities and age cutoffs from 5217 individuals in the German Chronic Kidney Disease cohort. We identified 33 pathogenic variants. Of these 27 (81.8%) were in COL4A3/4/5, the largest group being 15 COL4A5 variants with nine unrelated individuals carrying c.1871G>A, p.(Gly624Asp). We found three cysteine variants in UMOD, a novel missense and a novel splice variant in HNF1B and the homoplastic MTTF variant m.616T>C. Copy-number analysis identified a heterozygous COL4A5 deletion, and a HNF1B duplication/deletion, respectively. Overall, pathogenic variants were present in 12.5% (34/271) and variants of unknown significance in 9.6% (26/271) of selected individuals. Bioinformatic predictions paired with gold standard diagnostics for MUC1 (SNaPshot) could not identify the typical cytosine duplication ("c.428dupC") in any individual, implying that ADTKD-MUC1 is rare. Our study shows that >10% of selected individuals carry disease-causing variants in genes partly associated with tubulointerstitial kidney diseases. COL4A3/4/5 genes constitute the largest fraction, implying they are regularly overlooked using clinical Alport syndrome criteria and displaying the existence of phenocopies. We identified variants easily missed by some ES pipelines. The clinical filtering criteria applied enriched for an underlying genetic disorder.
CRIS-Team WoS Importer:2022-09-23

Single molecule real time sequencing in ADTKD-MUC1 allows complete assembly of the VNTR and exact positioning of causative mutations - Wenzel, Andrea; Altmueller, Janine; Ekici, Arif Bülent; Popp, Bernt; Stueber, Kurt; Thiele, Holger; Pannes, Alois; Staubach, Simon; Salido, Eduardo; Nuernberg, Peter; Reinhardt, Richard; Reis, André; et al. (Scientific Reports, 2018)
Recently, the Mucin-1 (MUC1) gene has been identified as a causal gene of autosomal dominant tubulointerstitial kidney disease (ADTKD). Most causative mutations are buried within a GC-rich 60 basepair variable number of tandem repeat (VNTR), which escapes identification by massive parallel sequencing methods due to the complexity of the VNTR. We established long read single molecule real time sequencing (SMRT) targeted to the MUC1-VNTR as an alternative strategy to the snapshot assay. Our approach allows complete VNTR assembly, thereby enabling the detection of all variants residing within the VNTR and simultaneous determination of VNTR length. We present high resolution data on the VNTR architecture for a cohort of snapshot positive (n = 9) and negative (n = 7) ADTKD families. By SMRT sequencing we could confirm the diagnosis in all previously tested cases, reconstruct both VNTR alleles and determine the exact position of the causative variant in eight of nine families. This study demonstrates that precise positioning of the causative mutation(s) and identification of other coding and noncoding sequence variants in ADTKD-MUC1 is feasible. SMRT sequencing could provide a powerful tool to uncover potential factors encoded within the VNTR that associate with intra- and interfamilial phenotype variability of MUC1 related kidney disease.
EVALuna2:34138

SWI/SNF protein expression status in fumarate hydratase-deficient renal cell carcinoma: immunohistochemical analysis of 32 tumors from 28 patients - Agaimy, Abbas; Amin, Mahul B.; Gill, Anthony; Popp, Bernt; Reis, André; Berney, Daniel M.; Magi-Galluzzi, Cristina; Sibony, Mathilde; Smith, Steven C.; Suster, Saul; Trpkov, Kiril; Hes, Ondrej; et al. (Human Pathology, 2018)
Fumarate hydratase-deficient renal cell carcinoma (FH-RCC) is a rare, aggressive RCC type, originally described in the setting of hereditary leiomyomatosis and RCC syndrome, which is defined by germline FH gene inactivation. Inactivation of components of the switch/sucrose nonfermentable (SWI/SNF) chromatin remodeling complex is involved in renal medullary carcinoma (SMARCB1/INI1 loss), clear cell RCC (PBRM1 loss), and subsets of dedifferentiated RCC of clear cell, chromophobe, and papillary types (loss of different SWI/SNF components). FH-RCC and SWI/SNF-deficient RCC share anaplastic nuclear features and highly aggressive course. We analyzed 32 FH-RCCs from 28 patients using 7 commercially available SWI/SNF antibodies (SMARCB1/INI1, SMARCA2, SMARCA4, SMARCC1, SMARCC2, PBRM1, and ARID1A). Variable loss of SMARCB1, ARID1A, and SMARCC1 was observed in 1 of 31, 2 of 31, and 1 of 29 evaluable cases, respectively; 3 of these 4 SWI/SNF-deficient tumors had confirmed FH mutations. No correlation of SWI/SNF loss with solid or sarcomatoid features was observed. Two tumors with SMARCB1 and ARID1A deficiency had available SWI/SNF molecular data; both lacked SMARCB1 and ARID1A mutations. The remaining 5 SWI/SNF components were intact in all cases. Especially PBRM1 seems not to be involved in the pathogenesis or progression of FH-RCC. Our data showed that a subset of FH-RCC (12%) have a variable loss of SWI/SNF complex subunits, likely as secondary genetic events. This should not be confused with SWI/SNF-deficient RCC of other types. Evaluation of FH and SWI/SNF together with comprehensive molecular genetic profiling is needed to explore possible prognostic implications of FH/SWI-SNF double deficiency and to better understand the somatic mutation landscape in high-grade RCC.
EVALuna2:34610

Targeted sequencing of FH-deficient uterine leiomyomas reveals biallelic inactivating somatic fumarase variants and allows characterization of missense variants - Popp, Bernt; Erber, Ramona; Kraus, Cornelia; Vasileiou, Georgia; Hoyer, Juliane; Burghaus, Stefanie; Hartmann, Arndt; Beckmann, Matthias; Reis, André; Agaimy, Abbas (Modern Pathology, 2020)
Uterine leiomyomas (ULs) constitute a considerable health burden in the general female population. The fumarate hydratase (FH) deficient subtype is found in up to 1.6% and can occur in hereditary leiomyomatosis and renal cell carcinoma (HLRCC) syndrome. We sequenced 13 FH deficient ULs from a previous immunohistochemical screen using a targeted panel and identified biallelic FH variants in all. In eight, we found an FH point mutation (two truncating, six missense) with evidence for loss of the second allele. Variant allele-frequencies in all cases with a point mutation pointed to somatic variants. Spatial clustering of the identified missense variants in the lyase domain indicated altered fumarase oligomerization with subsequent degradation as explanation for the observed FH deficiency. Biallelic FH deletions in five tumors confirm the importance of copy number loss as mutational mechanism. By curating all pathogenic FH variants and calculating their population frequency, we estimate a carrier frequency of up to 1/2,563. Comparing with the prevalence of FH deficient ULs, we conclude that most are sporadic and estimate 2.7–13.9% of females with an FH deficient UL to carry a germline FH variant. Further prospective tumor/normal sequencing studies are needed to develop a reliable screening strategy for HLRCC in women with ULs.
CRIS-Team Scopus Importer:2020-07-10

The mutational and phenotypic spectrum of TUBA1A-associated tubulinopathy - Hebebrand, Moritz; Hüffmeier, Ulrike; Trollmann, Regina; Hehr, Ute; Uebe, Steffen; Ekici, Arif Bülent; Kraus, Cornelia; Krumbiegel, Mandy; Reis, André; Thiel, Christian; Popp, Bernt (Orphanet Journal of Rare Diseases, 2019)
BackgroundThe TUBA1A-associated tubulinopathy is clinically heterogeneous with brain malformations, microcephaly, developmental delay and epilepsy being the main clinical features. It is an autosomal dominant disorder mostly caused by de novo variants in TUBA1A.ResultsIn three individuals with developmental delay we identified heterozygous de novo missense variants in TUBA1A using exome sequencing. While the c.1307G>A, p.(Gly436Asp) variant was novel, the two variants c.518C>T, p.(Pro173Leu) and c.641G>A, p.(Arg214His) were previously described. We compared the variable phenotype observed in these individuals with a carefully conducted review of the current literature and identified 166 individuals, 146 born and 20 fetuses with a TUBA1A variant. In 107 cases with available clinical information we standardized the reported phenotypes according to the Human Phenotype Ontology. The most commonly reported features were developmental delay (98%), anomalies of the corpus callosum (96%), microcephaly (76%) and lissencephaly (agyria-pachygyria) (70%), although reporting was incomplete in the different studies. We identified a total of 121 specific variants, including 15 recurrent ones. Missense variants cluster in the C-terminal region around the most commonly affected amino acid position Arg402 (13.3%). In a three-dimensional protein model, 38.6% of all disease-causing variants including those in the C-terminal region are predicted to affect the binding of microtubule-associated proteins or motor proteins. Genotype-phenotype analysis for recurrent variants showed an overrepresentation of certain clinical features. However, individuals with these variants are often reported in the same publication.ConclusionsWith 166 individuals, we present the most comprehensive phenotypic and genotypic standardized synopsis for clinical interpretation of TUBA1A variants. Despite this considerable number, a detailed genotype-phenotype characterization is limited by large inter-study variability in reporting.
CRIS-Team WoS Importer:2019-02-27

TRIM28 haploinsufficiency predisposes to Wilms tumor - Diets, Illja J.; Hoyer, Juliane; Ekici, Arif Bülent; Popp, Bernt; Hoogerbrugge, Nicoline; van Reijmersdal, Simon V.; Bhaskaran, Rajith; Hadjihannas, Michel; Vasileiou, Georgia; Thiel, Christian; Seven, Didem; Uebe, Steffen; et al. (International Journal of Cancer, 2019)
Two percent of patients with Wilms tumors have a positive family history. In many of these cases the genetic cause remains unresolved. By applying germline exome sequencing in two families with two affected individuals with Wilms tumors, we identified truncating mutations in TRIM28. Subsequent mutational screening of germline and tumor DNA of 269 children affected by Wilms tumor was performed, and revealed seven additional individuals with germline truncating mutations, and one individual with a somatic truncating mutation in TRIM28. TRIM28 encodes a complex scaffold protein involved in many different processes, including gene silencing, DNA repair and maintenance of genomic integrity. Expression studies on mRNA and protein level showed reduction of TRIM28, confirming a loss-of-function effect of the mutations identified. The tumors showed an epithelial-type histology that stained negative for TRIM28 by immunohistochemistry. The tumors were bilateral in six patients, and 10/11 tumors are accompanied by perilobar nephrogenic rests. Exome sequencing on eight tumor DNA samples from six individuals showed loss-of-heterozygosity (LOH) of the TRIM28-locus by mitotic recombination in seven tumors, suggesting that TRIM28 functions as a tumor suppressor gene in Wilms tumor development. Additionally, the tumors showed very few mutations in known Wilms tumor driver genes, suggesting that loss of TRIM28 is the main driver of tumorigenesis. In conclusion, we identified heterozygous germline truncating mutations in TRIM28 in 11 children with mainly epithelial-type Wilms tumors, which become homozygous in tumor tissue. These data establish TRIM28 as a novel Wilms tumor predisposition gene, acting as a tumor suppressor gene by LOH.
CRIS-Team Scopus Importer:2019-05-02
Keywords: genetic predisposition; haploinsufficiency; TRIM28; Wilms tumor

Tumor microenvironment-dependent epigenetic imprinting in the vasculature predicts colon cancer outcome - Naschberger, Elisabeth; Fuchs, Maximilian; Dickel, Nicholas; Kunz, Meik; Popp, Bernt; Anchang, Charles Gwellem; Demmler, Richard; Lyu, Yanmin; Uebe, Steffen; Ekici, Arif Bülent; Geppert, Carol-Immanuel; Hartmann, Arndt; et al. (Cancer Communications, 2023)
CRIS-Team Scopus Importer:2023-10-27

Whole exome sequencing reveals a novel de novo FOXC1 mutation in a patient with unrecognized Axenfeld-Rieger syndrome and glaucoma - Pasutto, F.; Mauri, L.; Popp, Bernt; Sticht, Heinrich; Ekici, Arif Bülent; Piozzi, E.; Bonfante, A.; Penco, Silvana; Schlötzer-Schrehardt, Ursula; Reis, André (Gene, 2015)
We report the identification of a novel mutation in the fork-head box C1 (FOXC1) gene which occurred de novo in an Italian patient with unrecognized Axenfeld-Rieger syndrome. He was previously diagnosed as having late recognized primary congenital glaucoma at the age of 14 years and was subsequently subjected to multiple surgical interventions due to uncontrolled intraocular pressure and progressive visual field loss. After exclusion of mutations in CYP1B1 and MYOC, trio-whole-exome sequencing revealed de novo in frame deletion in the coding region of the FOXC1 gene (c.407_409delGTC, p.V137del) leading to a deletion of the evolutionary conserved amino acid Valine at position 137 of the protein. Molecular modeling predicted that Val137 deletion impairs FOXC1 DNA-binding capacity and transcriptional activation. Since loss-of-function mutations in FOXC1 are associated with Axenfeld-Rieger syndrome, the genetic findings in combination with re-evaluation of the patient's clinical data resulted in a corrected diagnosis of Axenfeld-Rieger syndrome with developmental glaucoma. We therefore suggest that in addition to CYP1B1 and MYOC, FOXC1 should be included in the genetic analysis of cases with unclear glaucomatous phenotypes to ensure proper diagnosis, adequate treatment and appropriate genetic counseling.
EVALuna2:9257

ZMYND11 variants are a novel cause of centrotemporal and generalised epilepsies with neurodevelopmental disorder - Oates, Stephanie; Absoud, Michael; Goyal, Sushma; Bayley, Sophie; Baulcomb, Jennifer; Sims, Annemarie; Riddett, Amy; Allis, Katrina; Brasch-Andersen, Charlotte; Balasubramanian, Meena; Bai, Renkui; Callewaert, Bert; et al. (Clinical Genetics, 2021)
ZMYND11 is the critical gene in chromosome 10p15.3 microdeletion syndrome, a syndromic cause of intellectual disability. The phenotype of ZMYND11 variants has recently been extended to autism and seizures. We expand on the epilepsy phenotype of 20 individuals with pathogenic variants in ZMYND11. We obtained clinical descriptions of 16 new and nine published individuals, plus detailed case history of two children. New individuals were identified through GeneMatcher, ClinVar and the European Network for Therapies in Rare Epilepsy (NETRE). Genetic evaluation was performed using gene panels or exome sequencing; variants were classified using American College of Medical Genetics (ACMG) criteria. Individuals with ZMYND11 associated epilepsy fell into three groups: (i) atypical benign partial epilepsy or idiopathic focal epilepsy (n = 8); (ii) generalised epilepsies/infantile epileptic encephalopathy (n = 4); (iii) unclassified (n = 8). Seizure prognosis ranged from spontaneous remission to drug resistant. Neurodevelopmental deficits were invariable. Dysmorphic features were variable. Variants were distributed across the gene and mostly de novo with no precise genotype–phenotype correlation. ZMYND11 is one of a small group of chromatin reader genes associated in the pathogenesis of epilepsy, and specifically ABPE. More detailed epilepsy descriptions of larger cohorts and functional studies might reveal genotype–phenotype correlation. The epileptogenic mechanism may be linked to interaction with histone H3.3.
CRIS-Team Scopus Importer:2021-07-30
Keywords: antiepileptic drug; autism; bromodomain; comorbidity; EEG; epigenetic; histone H3.3; seizure